Morphology of some Bamboos Commonly Used in Lao PDR - Chaiyalad, Singkone; Sungkaew, Sarawood; Sripatanadilok, Somkid (วารสารวนศาสตร์ไทย, 2022)
Bamboos have provided a variety of raw materials and products widely used in Lao PDR for centuries. Their diversity often makes people confused particularly in local and botanical names. This study aimed to use the morphological procedure to identify some bamboos commonly used in the country. Three study sites (Oudomxay province, Vientiane Capital, and Champasak province) representing the Northern, Central, and Southern regions, respectively, were chosen as the representatives of the country. Ten species from six genera were found as follows: they are Bambusa blumeana, B. tulda, B. polymorpha, Dendrocalamus brandisii, D. membranaceus, Gigantochloa albociliata, Indosasa sinica, Schizostachyum sp., S. virgatum, Thyrsostachys siamensis. Their diagnostic morphological characters have a potential reference source for the identification of bamboos in their products and botanical names. Their diagnostic morphological characters, uses, and habitats were provided. Keywords: bamboos, Lao PDR, morphology, uses